Survey of research on Tor-based anonymous networking technologies - ZHU Yufei; HU Yuxiang; CHEN Bo; SHEN Juan; CUI Pengshuai; YUAN Zheng; TIAN Le (Tongxin xuebao)
In recent years, with the continuous development of network attack techniques, anonymous network technologies represented by Tor have faced performance bottlenecks and security challenges. To this end, a systematic review of the Tor anonymity communication mechanism, as well as its performance and security issues, has been conducted with a focus on the sender anonymity in the Tor network. First, key mechanisms, including the directory protocol, path selection, and circuit construction were analyzed to identify major issues in existing research, and corresponding optimization methods and improvement directions were summarized. Next, typical de-anonymization attacks, including both active and passive methods, were systematically reviewed, and the effectiveness of defense strategies against these attacks were analyzed. Finally, Tor’s limitations in terms of anonymity, security and performance were thoroughly examined, optimization strategies were summarized, and future research directions in the development of anonymous network technologies were prospected.